CURRENT STATUS OF IODINE-DEFICIENCY DISEASES - V.M. Krasnov (Union of pediatricians of Russia, 2010)
The article focuses on the issue of iodine-deficiency pathology. It provides historical background on this issue and reviews the progress made abroad in preventing iodine deficiency. It proposes specific steps to resolve the issue of iodine-deficient diseases in Russia. Key words: iodine deficiency diseases, goiter, iodine deficiency, iodized salt. (Pediatric Pharmacology. - 2010; 7(1):108-112)